THE EFFECTIVENESS OF SELF-AFFIRMATION TECHNIQUES AGAINST CLINICAL PRACTICE ANXIETY IN NURSE PROFESSIONAL STUDENTS AT STIKES PAYUNG NEGERI PEKANBARU - Fortunada, Yefrina; Febtrina, Rizka; Maulinda, Dini; Arfina, Angga (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: Nursing students often experience anxiety due to various factors, one of which is clinical practice anxiety for fear of making mistakes, worry during clinical practice due to lack of trust in one's own abilities, lack of knowledge due to online learning and lack of experience at the first time of clinical practice. One way to overcome clinical practice anxiety is to be given a Self-affirmation technique. Self-affirmation is converting negative thoughts into positive thoughts. The purpose of this study was to determine the effectiveness of the self-affirmation technique on clinical practice anxiety in students of the nursing program at STIKes Payung Negeri Pekanbaru. Method: Design of this study was quasi-experiment pre and post-test without control. The research location is at STIKes Payung Negeri Pekanbaru. The respondents were 18 nursing students program. The study was conducted from May 31 to June 7, 2022. Self-affirmation intervention is applied twice a day morning and evening for 5 minutes for 7 days. The anxiety research instrument used the Depression Anxiety Stress Scale (DASS) 42 questionnaire while self-affirmation used standard operational procedure. Result: The results of the univariate analysis showed that the anxiety score before intervention is 12.94 and decreased to 9.00 after being given self-affirmation. The results of the paired t-test showed p value is 0.000 which means that the self-affirmation technique is effective against clinical practice anxiety in nursing students at STIKes Payung Negeri Pekanbaru. Conclusion: Self affirmation can be used to address anxiety in nursing students who are running a clinical practice.